Type 1 diabetes incidence during COVID-19 pandemic has not been influenced by COVID-19 vaccination in northern Italy region, Lombardy. - Chiara Mameli; Camilla Valsecchi; Danilo Cereda; Simona Scarioni; Lucia Barcellini; Catia Boriello; Riccardo Bonfanti; Ilaria Brambilla; Valeria Calcaterra; Elena Calzi; Roberta Cardani; Anna Cogliardi; et al. (PLoS ONE)
Objective To describe the trends of type 1 diabetes(T1D) incidence in 0-17-year-olds over the years 2020-2023, and the COVID-19 vaccination uptake in Lombardy region. Methods Data about children and adolescents aged 0-17 years who received a diagnosis of T1D from 2020 to 2023 were extracted from the public computerized registry of the healthcare system of the Lombardy Region (Italy). After calculating the annual T1D incidence, the incidence in 2020, prior to the availability of vaccination, was compared to subsequent years. A separate analysis was conducted for the 12-17 age group, the first to receive vaccination. Results One thousand two hundred seventy-three T1D onsets were recorded. The distribution of T1D showed no significant annual variation by sex (p-trend = 0.338), mean age (9 years, p = 0.537) and age distribution (p-trend = 0.563). T1D incidence [95% CI/100.000] did not significantly change comparing 2020 [18.94/100.000 (CI 16.88-21.18)] with 2021 [21.82/100.000 (CI 18.90-23.44)], 2022 [20.77/100.000 (CI 18.59-23.13)] and 2023 [19.68/100.000 (CI 16.61-20.94)]. No differences in incidence were observed in the 12-17 age group during 2021-2023 when COVID-19 vaccination was available when compared to 2020 (p-wald > 0.05). The COVID-19 vaccination coverage was lower in children with diabetes onset compared to the same-age general population (38 vs 42%). Conclusions The incidence of T1D in children remained stable during the COVID-19 pandemic, regardless of the uptake of the vaccination.